Case report: (Pre)syncopal symptoms associated with a negative internal jugular venous pressure - Olesen, Niels D.; van Lieshout, Johannes J.; Fisher, James P.; Seifert, Thomas; Nielsen, Henning B.; Secher, Niels H. (Frontiers in Physiology, 2014)
A siphon is suggested to support cerebral blood flow but appears generally not to be established because internal jugular venous (IJV) pressure is close to zero iA siphon is suggested to support cerebral blood flow but appears not to be established because internal jugular venous (IJV) pressure is close to zero in upright humans. Thus in eleven young healthy males, IJV pressure was 9 ± 1 mmHg (mean ± SE) when supine and fell to 3 ± 1 mmHg when seated, and middle cerebral artery mean blood velocity (MCA Vmean; P < 0.007) and the near-infrared spectroscopy-determined frontal lobe oxygenation (ScO¬2; P = 0.028) also decreased. Another subject, however, developed (pre)syncopal symptoms while seated and his IJV pressure decreased to -17 mmHg. Furthermore, his MCA Vmean decreased and yet within the time of observation ScO¬2 was not necessarily affected. These findings support the hypothesis that a negative IJV pressure that is a prerequisite for creation of a siphon provokes venous collapse inside the dura, and thereby limits rather than supports CBF.  n upright humans. In eleven young healthy males, IJV pressure was 9 ± 1 mmHg (mean ± SE) when supine and fell to 3 ± 1 mmHg when seated, and middle cerebral artery mean blood velocity (MCA Vmean; P < 0.007) and near-infrared spectroscopy-determined frontal lobe oxygenation (ScO¬2; P = 0.028) also decreased. Another subject, however, developed (pre)syncopal symptoms while seated and his IJV pressure decreased to -17 mmHg. Furthermore, his MCA Vmean decreased and yet within the time of observation ScO¬2 was not necessarily affected. These findings suggest that a negative venous pressure affects rather than supports cerebral blood flow, maybe because a negative IJV pressure is transmitted to subdural veins and makes them collapse disrupting a siphon mechanism.